CENTRAL BANK REACTION TO PUBLIC DEFICIT AND SOUND PUBLIC FINANCE: THE CASE OF THE EUROPEAN MONETARY UNION - Canale, Rosaria Rita (Journal of Advanced Studies in Finance; Vol 1 No 1 (2010): JASF Volume I Issue 1 Summer 2010, 2010)
The paper aims to shed light on the relation between monetary and fiscal policy in EMU, focusing on the interest rates and deficit dynamics. We present a theoretical model in which monetary and fiscal policy independently interact through their own instrument, namely, the rate of interest for the central bank and deficit spending for governments. We demonstrate that the possibility of the two policy authorities producing not conflicting results depends on the idea each has of the workings of the economic system and on the influence each variable has on inflation and equilibrium income. Furthermore the inflationary opinion of the ECB about deficit spending leads to the result that public finance becomes surely unsound, unless governments stop using expansionary instruments. We provocatively conclude that the limits set by the Maastricht Treaty are a necessary solution to avoid unsound public finance.